Loss of teeth. Risk factors, prevalence, etiology, relationship with somatic pathology (literature review). - Doroshenko, О. М.; Shepelynskyi, О. В. (Actual Dentistry, 2024)
Introduction. According to the World Health Organization (WHO), a key aspect of oral health is the lifelong preservation of a functional dentition consisting of at least 20 teeth without the need for replacement. Tooth loss is one of the most common conditions that affects millions of people worldwide and is associated with a higher risk of mortality and systemic diseases, leads to functional, aesthetic and social impairments, reduces the quality of human life and can be an effective determinant of oral health. cavity of the population. Purpose: based on a thorough analysis of literary sources, to study the risk factors, prevalence, etiology of tooth loss and its connection with somatic pathology. Materials and methods. Information search and analysis of scientific sources using scientometric databases Web of Science, PubMed, Google Scholar over the past 15 years. Conclusion. The analysis of the literature data of recent years has shown the high prevalence of tooth loss in dental patients and the need to develop and implement modern multidisciplinary approaches to the treatment of this contingent of patients in health care practice.